Women Representatives in Britain, France, and the United States - Applewhite, Harriet Branson (Palgrave Macmillan, 2015)
"This book compares British, French, and American legislative debates on woman suffrage and women's rights. Beginning with an analysis of Tocqueville and J.S. Mill on the impact of suffrage, the book continues with analysis of floor debates, comparing gender style, the French on parity and the Americans on the ERA and concluding with modern debates"--
Keywords: France; Women; France; Women legislators; Great Britain; Women; Great Britain; Women legislators; History; Women; Suffrage; United States; United States; Women legislators; Women; dept.psc; faculty_collection

Political Alignment in the French National Assembly, 1789-1791 - Applewhite, Harriet Branson (Louisiana State University Press, 1993)
In this richly detailed study Harriet B. Applewhite analyzes the political alignment and loyalties of the deputies elected to the Estates General/National Assembly between 1789 and 1791. Her purpose is to understand how these men shaped the struggle that transformed France's constitutional structure and invented its modern political practices., To gauge the deputies' political alignments, Applewhite establishes categories based on their voting records, club memberships, signatures on protest lists, assessments by contemporary observers, and other evidence. She then arranges on a left-to-right scale all 1,318 of these individuals. For a selected group of deputies she uses published political pamphlets and biographical records not only to assess and compare their attitudes on issues concerning political legitimacy and political participation but also to establish and analyze connections between these attitudes and actual political behavior., Applewhite's investigation focuses on the origins of the deputies' understanding of French national unity, the nature and basis of the fierce partisan battles that raged in the National Assembly, and the changes in political institutions and practices that were handed down to postrevolutionary France. Contrary to the converging-elites theory popular among many students of the French Revolution, Applewhite finds that membership in one of the three estates of the Old Regime - the clergy, the aristocracy, and the commonalty - channeled the early careers of future deputies, their subsequent political opportunities, and their responses to the power struggles of the National Assembly., Applewhite defines two key legacies of the first National Assembly for the future of French legislative politics: first, a reluctance to compromise and an absence of trust that developed among participants at the outset and hardened throughout the twenty-eight months of the assembly; second, the development of a left, center, and right political culture within the National Assembly and a style of conflict that pulled both leaders and followers away from the center. This meticulously researched and carefully written work makes a significant and lasting contribution to the study of the French Revolution and points to new avenues of inquiry.--(Source of description unspecified.)
Keywords: 1789-1799; 18th century; France; France; France. Assemblée nationale constituante (1789-1791); History; History; France. États généraux; History; Legislators; Politics and government; award_winner; dept.psc; faculty_collection

Women and Politics in the Age of the Democratic Revolution - Applewhite, Harriet Branson; Levy, Darline Gay (University of Michigan Press, 1990)
Keywords: 18th century; 18th century; Revolutions; 18th century; Women; Europe; History; Political activity; United States; Women; dept.psc; faculty_collection

Women in Revolutionary Paris, 1789-1795 - Levy, Darline Gay; Applewhite, Harriet Branson; Johnson, Mary Durham (University of Illinois Press, 1979)
"Almost 200 years ago, the women of revolutionary Paris were demanding legal equity in marriage; educational opportunities for girls, including vocational training ; public instruction, licensing, and support for midwives; guarantees for women's rights to employment; and an end to the exclusion of women from certain professions. The editors have uncovered, translated, and annotated sixty documents which shed light on these and other socioeconomic struggles by women and their impact on the French Revolutionary era. This work makes a significant contribution to the growing appreciation of the role of women in history, politics, ideology, and social change."--Back cover.
Keywords: France; History; Paris; Political activity; Revolution, 1789-1799; Sources; Sources; France; Sources; Women; Women's rights; dept.psc; faculty_collection